Personality and the Intention to use Bus Rapid Transit on Pandemic COVID-19: The role of environmental concern as a mediator - Shadiqi, Muhammad Abdan (UI Scholars Hub, 2023)
The COVID-19 pandemic has had an impact on the behavior of public transport users and raised concerns about the means of transportation. Therefore, this study aims to explain the mediating effect of environmental concern in the relationship between five personality traits on the intention to use Bus Rapid Transit (BRT) during the pandemic. A correlational survey of 425 participants was conducted, and the analysis found that all five personality traits did not directly predict the intention to use BRT. Furthermore, there was a positive mediating effect at the weak level of environmental concern on the relationship between four of the personality traits (agreeableness, conscientiousness, extraversion, and openness to experience) toward the intention to use BRT. The results showed that the mediating effect of environmental concern was not significant for the relationship between neuroticism and BRT usage intentions. It was reported that one of the reasons people use public transportation is due to environmental concerns during a pandemic.